Thermal treatment of the carbon nanotubes and their functionalization with styrene - de Falco, Alejandro Diego (2009)
In this work we studied the functionalization of commercially available multiwalled carbon nanotubes (MWCNT) (Nanocyl 3100) with polystyrene by the method so called "grafting from". The nanotubes were used as received and oxidized in air at 400 °C. The functionalization was started using thionyl chloride under reflux, followed by a reaction with ethylene glycol which allowed the inclusion of hydroxyl groups. The reaction of those with 2-chloropropionyl chloride led to the generation of the polymerization initiator. Last, the radical polymerization of the functionalized nanotubes, using styrene as the monomer, led to new materials which were studied with thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM) and ultraviolet-visible (UV-vis) spectroscopy. © 2009 Elsevier B.V. All rights reserved.